An interesting implantable cardioverter defibrillator treatment for lethal ventricular arrhythmias caused by coronary artery spasm: A case report. Issue 26 (June 2017) - Sun, Jie; Feng, Li; Li, Fei; Zhang, Yanchun; Dong, Jianting
Abstract: Rationale: Coronary artery spasm (CAS) could cause serious lethal ventricular arrhythmias. While implantable cardioverter defibrillators (ICDs) have been recommend for secondary prevention of sudden cardiac death related to lethal ventricular arrhythmias. However, in resuscitated sudden cardiac death caused by CAS, the effect of ICD is still not well clear. Patient Concerns: A 60-year-old male presented with 2 episodes of syncope. Coronary angiography showed normal coronary arteries. Twenty-four hour Holter electrocardiograms revealed that there were repeatedly transient marked ST segment elevation in the all leads except avR lead, junctional rhythm, and subsequently nonsustained ventricular tachycardia. Diagnoses: Ischemic-induced lethal ventricular arrhythmias caused by CAS. Interventions: Both calcium channel blocker (diltiazem, 180 mg twice daily) and nitrate (isosorbide dinitrate 40 mg twice daily) were initially administrated, and ICD was subsequently implanted as a secondary prevention. Outcomes: In the early stage of CAS, ICD therapy terminated the lethal ventricular arrhythmias. Conversely, after the administration of epinephrine, ICD therapy, even combined with external defibrillation, failed in resuscitating sudden cardiac death. Lessons: For the sudden cardiac death related to lethal ventricular arrhythmias caused by CAS, ICD therapy is an efficient secondary prevention base on administrating coronary vasodilators. Furthermore, administration of epinephrine should be avoided during cardiorespiratory resuscitation of sudden cardiac death caused by CAS.